Factive Presupposition in American Presidential War Speeches: Pragmatic perspective - Adeeb, Eman Riyadh (Al-Adab Journal, 2015)
This paper introduces our work on the pragmatic perspective of factive presupposition in American presidential war speeches .The major concern of this work is to highlight the significance of factuality in such selected speeches and its role in conveying certain messages .Pragmatics as a science has come to be applied to different practical domains depending on the view of the users ,especially , the aims and purposes they want to achieve .Presupposition is one of the essential topics in pragmatics; it has a great deal of importance in various fields as in religion ,law and politics. Thus, presuppositions is mainly and widely used and manipulated by many politicians. They are not allowed to make direct assertion or direct persuasion on their speeches .They tend to presuppose and use indirect constructions. Because presupposition is a main topic, which is widely used covertly, the politicians used factive presupposition frequently and excessively, especially in declaring war. The study, in the first part deals with factive presupposition and a general review of this phenomenon with factuality and factive constructions .Part two deals with politics and language ,then the last part which is dedicated to the practical implications and the analysis of factuality in the selected Americans presidential war speeches